Indikator yang Mempengaruhi Tingkat Ketahanan Pangan di Kabupaten Bungo Provinsi Jambi - F Fikriman; Candra Hermawanto; Asnawati Is (JURNAL GALUNG TROPIKA, 2020)
The purpose of this study is to know the value of the indicator of food security levels, to assess food security levels, and to understand the indicators that most affect food security levels in the bungo county of the jambi province. The basic method for this study is the institutional survey of taking secondary data to agencies in order to know the food security index.For data analysis using multiple liniear analysis. The accuracy of the model is tested using statistical tests, namely the t-test, F-count and coefficient of determination adjusted for R-sq. Studies indicate that there are 3 unequal indicators for food security: households with a proportion of 65% spending in their total coin income is quite poor (21.42%), women's education over 15 years of age (10%) and the health-care ratio of people to very low population densities (2.75). And the other 6 variables that have been consistent with the country's high surplus ratio of consumption to food production (0.038), people who live below the world's poverty line are resilient enough (10.11%), people with no access to electricity with extreme resistance (4.25%),Residents with no access to clean water in highly resistant conditions (39.39%), highly resilient predatives (18.24%) and highly resilient life expectancy at birth (99.74%).The food safety index in the bungo district is in a very resilient state with an index of 0.06. The indicator that particularly affects food security levels is the ratio per health-care to population density.